2021
DOI: 10.1200/op.20.00907
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Financial Distress and Quality of Life Over Time in Patients With Gynecologic Cancer—Making the Case to Screen Early in the Treatment Course

Abstract: PURPOSE: Our objective was to measure the trajectory of financial distress and to determine its relationship with quality of life (QOL) among patients with cancer. MATERIALS AND METHODS: We conducted a longitudinal survey of patients with gynecologic cancer starting a new line of systemic therapy at baseline, 3 months, and 6 months. Financial distress was measured using a Comprehensive Score for Financial Toxicity (COST) < 26, and QOL was measured using Functional Assessment of Cancer Therapy-General (FACT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
(27 reference statements)
1
9
0
2
Order By: Relevance
“…The women in our study reported comparable financial toxicity levels as prior studies reporting COST scores of gynecologic cancer survivors averaging two years post‐diagnosis (median = 29) 9 and worse financial toxicity than survivors of solid tumors 2‐year post‐treatment ( M = 32.5, SD = 9.46, range = 6–44) 24 . Other studies have used COST scores <26 and ≤23 as cut‐off points and found 49%–54% of gynecologic cancer survivors reported financial distress 25,26 ; compared to 45% in our sample with scores <26 (i.e., aligned with mild, moderate, and severe financial toxicity based on the COST grading system).…”
Section: Discussionsupporting
confidence: 72%
“…The women in our study reported comparable financial toxicity levels as prior studies reporting COST scores of gynecologic cancer survivors averaging two years post‐diagnosis (median = 29) 9 and worse financial toxicity than survivors of solid tumors 2‐year post‐treatment ( M = 32.5, SD = 9.46, range = 6–44) 24 . Other studies have used COST scores <26 and ≤23 as cut‐off points and found 49%–54% of gynecologic cancer survivors reported financial distress 25,26 ; compared to 45% in our sample with scores <26 (i.e., aligned with mild, moderate, and severe financial toxicity based on the COST grading system).…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, our included studies showed that the correlation strengths between financial toxicity and overall HRQOL were slightly stronger in studies that used English instruments (median = 0.53, range = 0.33-0.73) 57,58,60,62,64,66,73,81 than those in other languages, for example, Mandarin Chinese, Italian, and Arabic (median = 0.43, range = 0.34-0.52), 51,55,67,72,79,80 and conducted in countries with universal health coverage (median = 0.49, range = 0.34-0.73) 55,58,66,72,79,80 than those without (median = 0.42, range = 0.33-0.63). 51,57,60,62,64,67,73,81 Nevertheless, we had inadequate number of studies to further examine (eg, performing subgroup analysis) the potential impact of instrument language or universal health coverage on the association between financial toxicity and HRQOL. 46 Exploring the role of universal health coverage and mitigation strategies in alleviating financial toxicity and improving HRQOL may be an important future research direction.…”
Section: Discussionmentioning
confidence: 90%
“…1 An increasing amount of attention has been paid to FT in patients with cancer, in large part due to the rising costs of cancer diagnosis and treatment. 2 Previous studies of FT in cancer patients have examined the prevalence of FT among subgroups of patients with different cancer types, 3 , 4 , 5 , 6 cancer stages, 5 , 7 , 8 treatment schemes, 5 , 9 healthcare coverage systems, 10 , 11 , 12 or other subgroups as well as related factors of FT. These studies indicated disparities in prevalence and related factors among subgroups.…”
Section: Introductionmentioning
confidence: 99%